Radial growth of common horse chestnut in green plantings of Lviv and Kharkiv - Koval , I. M.; Chermnykh , M. O.; Gololobov, V. V. (Man and Environment. Issues of Neoecology, 2025)
Purpose. to identify the consequences of climate change and the invasion of the horse chestnut leaf miner on the radial growth of horse chestnut in green plantings of the cities of Lviv and Kharkiv. Methods. System analysis, dendrochronological and statistical methods were used. Results. The radial growth of trees in middle-aged plantings was compared for the period before the outbreak of the horse chestnut leaf miner (1982-2001) and after it (2002-2021) for Lviv and for 1990-2006 and 2007-2023 for Kharkiv. The temperatures for the hydrological year for these periods were also compared according to data from the Lviv and Kharkiv weather stations. It was found that in the second period Kharkiv was a decrease in growth by 57%. For the first period (before the outbreak), deviations from the norm of radial growth of common horse chestnut in the green plantation of Lviv were 12-23%, the corresponding values for the second period – 17-72%. It was found that in the second period in the Lviv plantation, the influence of temperatures on the radial growth of horse chestnut, in general, became more positive for different periods of the hydrological year. The number of positive correlation coefficients between radial growth and climatic factors also increased, which indicates an increase in the sensitivity of trees. In the green plantation of Kharkiv, when comparing the influence of climate on the radial growth of horse chestnut in 1986-2004, and 2005-2022 it was found that precipitation had a positive effect on growth, unlike temperature, which had a negative effect on radial growth. This is characteristic of both periods. Conclusions. When comparing the radial growth of horse chestnut for the periods before the beginning of the chestnut miner invasion (1982-2001) and after it (2002-2021) in Lviv and, respectively, for Kharkiv for 1986-2004 and 2005-2023, the decrease in growth was half as much in the second period compared to the first, despite the fact that the chestnut leaf miner arrived in Kharkiv 5 years later than in Lviv. Despite the significant decrease in radial growth due to climate change and the impact of the chestnut miner invasion, the radial growth of horse chestnut in the Lviv plantation stabilized during 2017–2021 and in the Kharkiv plantation – during 2016–2023. This indicates the adaptation of the horse chestnut to environmental changes at this stage.